O lugar das mulheres na História ensinada: o que nos dizem os saberes e práticas de professoras que atuam em escolas no município de Caldas Novas-GO - Ferreira, Juliana Kummer Perinazzo (2024)
This study was developed within the scope of the Knowledge and Educational Practices Line and the Study and Research Group on Geography and History Teaching (GEPEGH) of the Postgraduate Program at the Federal University of Uberlândia (PPGED/UFU), and it seeks to analyze in which place women are found in History taught in public schools in the city of Caldas Novas, GO. As key questions: do female History teachers, through their practices developed in everyday school life, problematize gender relations that are historically and socially constructed, or do they reaffirm standards imposed by society? How these female teachers thought about it and applied, in their classes, the approach to women's participation in History, their struggles for rights and representation in public spaces? What practices are planned by them, based on what knowledge, and what knowledge is debated and engendered in History classes with students? Is the movement to value the role of women in history happening both in academia and in schools? Is there a relationship between these places in contributing to the deconstruction of conservative knowledge and behaviors that are so crucial to the culture of patriarchy? The objective is to identify and analyze what knowledge is constructed and disseminated by female teachers, specifically History in the last years of Middle School, about female participation in History and gender relations. How they carry out their practices in the classroom related to the subject and the narratives they construct or select about the role of women in History. To develop this approach, we utilized educational investigations with a qualitative approach and theoretical-epistemological conceptions from the decolonial perspective that propose to examine, based on the practice of subjects in the environment in which they are inserted and no longer as objects. For data collection, the focus group technique was utilized within History teachers, with the research carried out in nine state schools and seven municipal schools, of which one was in rural areas and the rest in urban areas. For the discussions, decolonial feminism was introduced as a key concept in understanding gender coloniality, intersectionality and debates about school curricula. That said, we discussed how the knowledge and practices of female History teachers are produced and how teacher training can contribute to these discussions. Furthermore, cultural studies were inserted as contributions to understand the construction of knowledge based on what culture is and how culture shapes the formation of teachers' historical consciousness.